Design of a Health Monitoring System Based on NodeMCU and the Internet of Things (IoT) as a Mental Health Screening Tool for STMIK Widya Cipta Dharma Samarinda Students - Dair, Muhammad Filza Al; Pahrudin, Pajar; Salmon, Salmon (Sebatik, 2025)
University students’ mental health has become a critical concern within Indonesia’s higher education landscape. This study aims to design and develop a mental health monitoring system based on the technology at STMIK Widya Cipta Dharma Samarinda. The system utilizes a NodeMCU microcontroller integrated with heart rate and body temperature sensors to collect users’ physiological data in real-time. This information is displayed via an LCD screen and can be accessed wirelessly through a Wi-Fi-based application. The research methodology involves system design, hardware and software implementation, and functional testing through an experimental approach. The results indicate that the system is capable of accurately and reliably monitoring vital signs, making it a potentially effective early screening tool for identifying symptoms of mental health disorders such as stress and anxiety. This finding is expected to raise awareness among students regarding the importance of mental well-being and to encourage active participation in preventive efforts. Furthermore, the study paves the way for broader development of technology-based mental health monitoring systems that can be integrated with institutional psychological services.